WHEN CONCRETIZED EMOTION-BELIEF COMPLEXES DERAIL DECISION-MAKING CAPACITY - Halpern, Jodi (Bioethics, 2012)
There is an important gap in philosophical, clinical and bioethical conceptions of decision-making capacity. These fields recognize that when traumatic life circumstances occur, people not only feel afraid and demoralized, but may develop catastrophic thinking and other beliefs that can lead to poor judgment. Yet there has been no articulation of the ways in which such beliefs may actually derail decision-making capacity. In particular, certain emotionally grounded beliefs are systematically unresponsive to evidence, and this can block the ability to deliberate about alternatives. People who meet medico-legal criteria for decision-making capacity can react to health and personal crises with such capacity-derailing reactions. One aspect of this is that a person who is otherwise cognitively intact may be unable to appreciate her own future quality of life while in this complex state of mind. This raises troubling ethical challenges. We cannot rely on the current standard assessment of cognition to determine decisional rights in medical and other settings. We need to understand better how emotionally grounded beliefs interfere with decision-making capacity, in order to identify when caregivers have an obligation to intervene.